2018
DOI: 10.1371/journal.pone.0197860
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal impacts of pubertal timing and weight status on adolescent Internet use: Analysis from a cohort study of Taiwanese youths

Abstract: AimTo investigate the longitudinal impacts of pubertal timing and weight status on Internet use in adolescents.MethodsThree waves of data on a longitudinal cohort of 7th grade students (N = 2430) were retrieved from the Taiwan Youth Project. Univariate and multivariate regression models were applied using crude and adjusted odds ratios (OR) with 95% confidence intervals (CI) to examine the concomitant impacts of pubertal timing and weight status on adolescent Internet use.ResultsThe dataset identified 210 (8.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…Adolescence covers the period when people become independent individuals, establish new relationships, develop social skills, and learn behaviors for the rest of their lives. In this period of neurological, physical, and emotional transition from childhood to adulthood, young people face a range of health risks (1)(2)(3). They are often exposed to many health risks such as injuries, malnutrition, addiction to tobacco, alcohol and drugs, video games, sexually transmitted diseases, or teenage pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence covers the period when people become independent individuals, establish new relationships, develop social skills, and learn behaviors for the rest of their lives. In this period of neurological, physical, and emotional transition from childhood to adulthood, young people face a range of health risks (1)(2)(3). They are often exposed to many health risks such as injuries, malnutrition, addiction to tobacco, alcohol and drugs, video games, sexually transmitted diseases, or teenage pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that the pubertal development of girls in the 'Social Screens' segment was more advanced than that of girls in 'the Mainstream' segment. There is evidence that early maturation is associated with increased internet use [49], and it has been suggested that youth are particularly vulnerable to social media influence due to extensive neural development that occurs during puberty [50]. This suggests that social media strategies may be effective in reaching early maturing adolescent girls, although messages must be carefully designed to highlight safe PA spaces for girls who may be self-conscious and fearful of judgement [51].…”
Section: Discussionmentioning
confidence: 99%
“…Male adolescents were more likely to overindulge on the Internet because of depression. Female adolescents were more prone to depression as a result of Internet addiction (Tsai et al, 2018;Liang et al, 2016).…”
Section: Psychiatric Factor Related To Internet Addictionmentioning
confidence: 99%
“…When weight status and pubertal timing were considered, sexual maturation came in as an important confounder in the link between the purposes of Internet use and weight status. Meanwhile, the gender difference was noted in the association between adolescent weight status and Internet use (Tsai et al, 2018). The causal relationship between Internet addiction and depression varies by gender.…”
Section: Psychiatric Factor Related To Internet Addictionmentioning
confidence: 99%